RAD-Seq derived markers flank the shell colour and banding loci of the Cepaea nemoralis supergene - Richards, Paul M.; Liu, M. Maureen; Lowe, Natalie; Davey, John W.; Blaxter, Mark L.; Davison, Angus (Wiley, 2013)
Studies on the classic shell colour and banding polymorphism of the land snail Cepaea played a crucial role in establishing the importance of natural selection in maintaining morphological variation. Cepaea is also a pre-eminent model for ecological genetics because the outward colour and banding phenotype is entirely genetically determined, primarily by a ‘supergene’ of at least five loci. Unfortunately, progress in understanding the evolution and maintenance of the Cepaea polymorphism stalled, partly because of a lack of genetic markers. With a view to re-establish Cepaea as a prominent model of molecular ecology, we made six laboratory crosses of Cepaea nemoralis, five of which segregated for shell ground colour (C) and the presence or absence of bands (B). First, scoring of colour and banding in 323 individuals found no recombination between the C and B loci of the supergene. Second, using restriction site–associated DNA sequencing (RAD-Seq) of two parents and 22 offspring, we identified 44 anonymous markers putatively linked to the colour (C) and banding (B) loci. The genotype of eleven of the most promising RAD-Seq markers was independently validated in the same 22 offspring, then up to a further 146 offspring were genotyped. The closest RAD-Seq markers scored are within ~0.6 centimorgan (cM) of the C-B supergene linkage group, with the combined loci together forming a 35.8 cM linkage map of markers that flank both sides of the Cepaea C-B supergene.